Essays in Donor Funded Interventions and the Activities of A Professional Accountancy Organisation in Ghana - Fosu, R.A. (University of Ghana, 2019)
The effect of donor-funded interventions has been a subject of long standing debate over several years of donor support. This thesis focuses on donor-funded interventions and the activities of a professional accountancy organisation in Ghana. Specifically, the thesis explores and analyses how donor-funded interventions have influence the activities of a professional accountancy organisation in Ghana as well as soliciting the perceptions of stakeholders about the outcomes of the interventions. The present thesis adopts a mix of qualitative and quantitative approaches; conducted interviews with key actors in the implementation of the interventions and administered questionnaires to selected stakeholders of the professional accountancy organisation. Thematic analysis was used in the analysis of the data collected through interviews with the respondents, while regression and structural equation modelling technique were used to analyse the quantitative data. The empirical results show a general acknowledgement among the respondents of the positive effect of the intervention on the activities of the professional accountancy organisation (PAO). However, the biggest challenge encountered in the implementation of the funded intervention is the counterpart funding provided by the PAO. Furthermore, continual professional development (CPD) quality, exams quality and tuition quality are key drivers of a credible professional qualification. Thus, an improvement in these drivers leads to an enhancement of the credibility of a professional qualification. This result is novel because to the best of the author’s knowledge; this is the first time a study has empirically tested this construct. Third, donor funded training interventions improved the competencies and organisational commitment of the respondents. The thesis makes several contributions to the accounting literature: First, the thesis enriches the accounting literature by providing a drive for a renewed attention by scholars on the activities of professional accountancy organisations which hitherto has overly University of Ghana http://ugspace.ug.edu.gh iv focused on international accounting firms. Second, soliciting the perceptions of key stakeholders is important at addressing the long held view by scholars that evaluations of donor interventions often do not take into account wider stakeholder feedback. Furthermore, the findings from the thesis are relevant in shaping future donor policies aimed at improving the effectiveness of funded interventions. In conclusion, this thesis generates important public policy considerations. Donors and implementing agencies of intervention programmes should take into account the financial state of local accountancy bodies in future donor projects. This is because counterpart funding places a lot of stress on the finances of these bodies which sometimes leads to difficulties in programme execution. Also, the information communication technology (ICT) infrastructure of most developing countries is not well developed to support such interventions which are mostly ICT based. This poses a challenge to the successful implementation of donor projects. Furthermore, project designs should be sensitive to local circumstances of PAOs, as projects may fail to achieve the intended outcomes if the local circumstances are ignored.
PhD. Accounting
Keywords: Quantitative; Approaches; Professional; Organisation; Intervention